Direct observation of breaking of the intramolecular H-bond, and slowing down of the proton motion and tuning its mechanism in an HBO derivative1. Issue 22 (14th June 2015) - Alarcos, Noemí; Gutiérrez, Mario; Liras, Marta; Sánchez, Félix; Moreno, Miquel; Douhal, Abderrazzak
<x xml:space="preserve">Abstract</x> Exploring the mechanism of proton motion coupled to a charge-transfer reaction in a new HBO derivative in solution using steady-state and ultrafast emission spectroscopy shows an abnormal spectroscopic and dynamical behavior.